2015
DOI: 10.1002/zaac.201500576
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of an η2‐C, S‐Thioketene Complex in Pursuit of Tungsten(IV)‐Sulfanylalkyne Complexes

Abstract: The oxo tungsten(IV) alkyne complexes [Tp′W(O)(I)(η2‐C2Ph2)] (1), [Tp′W(O)(I){η2‐C2(SC2H4SiMe3)2}] (2), and [Tp′W(O)(I){η2‐C2(SBn)2}] (3) [Tp′ = hydridotris(3, 5‐dimethylpyrazolyl)borate, Bn = benzyl] were synthesized from [Tp′W(O)(CO)(I)]. All three compounds were fully characterized including structure determination by X‐ray diffraction analysis. Further elucidation of these reactions led to the isolation of several by‐products including an unexpected tungsten(IV) thioketene complex [Tp′W(O)(I){η2‐S = C=C(H)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[29,30] Due to the strong trans effect of the oxido ligand, the opposite metalÀ sulfur bond (2.6218(6) -2.6690(5) Å) is considerably longer than the other (2.4097(6) -2.4194(6) Å) in all presented complexes as already observed in [MoO (PMe 3 )(6-MePyS) 2 ]. [53] While W(IV) oxido C 2 R 2 complexes are already quite established, [19,21,45,54] the structures of complexes 6b, 7b, and 8b represent the first examples of Mo(IV) oxido C 2 R 2 complexes.…”
Section: Synthesis Of Oxido Complexesmentioning
confidence: 99%
“…[29,30] Due to the strong trans effect of the oxido ligand, the opposite metalÀ sulfur bond (2.6218(6) -2.6690(5) Å) is considerably longer than the other (2.4097(6) -2.4194(6) Å) in all presented complexes as already observed in [MoO (PMe 3 )(6-MePyS) 2 ]. [53] While W(IV) oxido C 2 R 2 complexes are already quite established, [19,21,45,54] the structures of complexes 6b, 7b, and 8b represent the first examples of Mo(IV) oxido C 2 R 2 complexes.…”
Section: Synthesis Of Oxido Complexesmentioning
confidence: 99%
“… 10 Analogous dimers are rare in tungsten chemistry due to the low redox potential of tungsten(VI) dioxido moieties. 11 15 Although some of the tungsten complexes turned out as bioinorganic models and catalysts for oxygenation reactions, those reactions have a low atom economy since the presence of terminal oxidants such as peroxides is always required. 6 , 16 Thus, investigating systems that utilize dioxygen or even air is highly desirable for economic and environmental reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, tungsten­(VI) and especially molybdenum­(VI) dioxido motifs have drawn much attention as models for different metalloenzymes which catalyze oxygen atom transfer (OAT) reactions. The major drawback of molybdenum OAT catalysts is their high tendency to form relatively inert molybdenum­(V) μ-oxo dimers, which appear as a result of comproportionation of molybdenum­(IV) oxido and molybdenum­(VI) dioxido species. The dinucleation can be inhibited by increasing the steric bulk of the ligands or immobilizing the active species to a polymeric support . Analogous dimers are rare in tungsten chemistry due to the low redox potential of tungsten­(VI) dioxido moieties. Although some of the tungsten complexes turned out as bioinorganic models and catalysts for oxygenation reactions, those reactions have a low atom economy since the presence of terminal oxidants such as peroxides is always required. , Thus, investigating systems that utilize dioxygen or even air is highly desirable for economic and environmental reasons . Although several tungsten complexes react with dioxygen, no homogeneous system is reported to utilize it catalytically.…”
Section: Introductionmentioning
confidence: 99%
“… 26 28 This may mainly be explained by the half-reaction of the catalytic cycle requiring reduction of the metal center ( Scheme 1 a), which is often challenging with tungsten due to its lower redox potential. 29 31 Possibly for these reasons, W(V) μ-oxo dimers are only known with scorpionate 32 , 33 and dithiocarbamate ligands, 34 , 35 besides an organometallic example. 36 Comparative studies revealing a higher OAT activity of the tungsten(VI) compound than that of the molybdenum analogue are extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten­(VI) models in OAT reactions are studied less and mainly alongside analogous molybdenum compounds. Such investigations revealed that analogous Mo­(IV, VI) and W­(IV, VI) complexes are nearly isostructural; however, lower or no catalytic activity of the tungsten system is usually observed. This may mainly be explained by the half-reaction of the catalytic cycle requiring reduction of the metal center (Scheme a), which is often challenging with tungsten due to its lower redox potential. Possibly for these reasons, W­(V) μ-oxo dimers are only known with scorpionate , and dithiocarbamate ligands, , besides an organometallic example . Comparative studies revealing a higher OAT activity of the tungsten­(VI) compound than that of the molybdenum analogue are extremely rare.…”
Section: Introductionmentioning
confidence: 99%